2013
DOI: 10.1177/1534735413503544
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Herbal Formula Induces Cell Cycle Arrest and Apoptosis in Association With Suppressing the PI3K/AKT Pathway in Human Lung Cancer A549 Cells

Abstract: Aim of the study. In recent years, the incidence of lung cancer, as well as the mortality rate from this disease, has increased. Moreover, because of acquired drug resistance and adverse side effects, the effectiveness of current therapeutics used for the treatment of lung cancer has decreased significantly. Chinese medicine has been shown to have significant antitumor effects and is increasingly being used for the treatment of cancer. However, as the mechanisms of action for many Chinese medicines are undefin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 40 publications
0
24
0
Order By: Relevance
“…Chinese Herb Medicine is one of the resources worthy to be explored for new treatment of cancer 21 . However, systematic investigation is necessary to ensure the practice of Chinese Herb Medicine to be evidence-based 2224 .…”
Section: Discussionmentioning
confidence: 99%
“…Chinese Herb Medicine is one of the resources worthy to be explored for new treatment of cancer 21 . However, systematic investigation is necessary to ensure the practice of Chinese Herb Medicine to be evidence-based 2224 .…”
Section: Discussionmentioning
confidence: 99%
“…Traditional Chinese Medicine is efficient in improving clinical symptoms, regulating tumor growth and preventing the recurrence of lung cancer in patients. In our previous study, we found that the "Ke Jinyan Priscription", given by the State Medical Master Zhou Zhongying, inhibited the proliferation of NCI-H157 or A549 transplanted tumors, respectively, in nude mice, and the physical status of the animals was significantly improved (4). Some ingredients extracted from the formula showed significant inhibitory effects on NSCLC cell lines under screening on the high-throughput platform (5,6).…”
Section: Introductionmentioning
confidence: 99%
“…Approximately 80 % of lung cancers are non-small cell lung cancer (NSCLC), most of which are subdivided into squamous cell carcinoma and adenocarcinoma [3]. Although surgery is the most effective curative treatment for early-stage NSCLC, up to 75 % of patients will present with advanced disease at diagnosis [4,5].…”
Section: Introductionmentioning
confidence: 99%